Analisis Potensi Penggunaan Media Sosial Instagram Untuk Pembelajaran Biologi Di SMAN 2 Padang - Rayhanna Fadillah S; Relsas Yogica (Journal on Education, 2024)
Instagram is one of the social media that is starting to become popular now after YouTube, WhatsApp and Facebook. According to Meta's advertising resources (2023), Instagram users in 2023 will be 89.15 million users in Indonesia. Instagram is a social media that has complete features. Instagram can take photos, videos and can provide filters on these photos and videos which can then be saved to the gallery and can also be uploaded to the Instagram social media account itself so that it can make it easier for teachers to assess the level of skills and creativity of students through photos and videos uploaded to the account. Instagram students. This research aims to find out how much potential there is for using Instagram social media for biology learning at SMAN 2 Padang. This research is descriptive research with a quantitative approach. Quantitative data was obtained through data from filling out questionnaires by a number of respondents, namely students of SMAN 2 Padang. Based on the results of data processing, it is known that Instagram has the potential (76.13%) to be used in biology teaching and learning activities, this is due to students' closeness to Instagram, ease of use and Instagram can also be used as a medium for searching for biology learning information. Therefore, biology teachers at SMAN 2 Padang can consider starting to use Instagram in biology lessons. Keywords: Social media, Instagram, Biology learning.